Characteristics of Binderless Particleboard Made of Three Species of Sulawesi Bamboos - Suhasman Suhasman; Detti Yunianti; Sahriyanti Saad; Baharuddin Baharuddin (Masyarakat Peneliti Kayu Indonesia, 2013)
Binderless particleboards (BP) were produced from three different species of Sulawesi bamboos. Parring bamboo (Gigantochloa ater) was extracted from Tanralili Maros while betung bamboo (Dendrocalamus asper) and tallang bamboo (Schizostacyum barcahycladum) were extracted from Batu Papan Makale Tana Toraja. The bark and nodes were removed, followed by cutting into chips; air drying, and finally converting into fine particles. The particles were oxidized using hydrogen peroxide 15% based on oven dry particle weight and 7.5% ferrous sulfat based on hydrogen peroxide weight. Hot pressing was applied for 12 min at 180ºC. Seven types of bamboo BP were produced based on the raw materials, i.e. the bamboo species namely; parring bamboo, betung bamboo, tallang bamboo, parring-betung bamboo with ratio 1 : 1, parring-tallang bamboo with ratio 1 : 1, betung-tallang bamboo with ratio 1 : 1, and parring-betung-tallang bamboo with ratio 1 : 1 : 1. The results indicated that the characteristics of betung bamboo BP were better than the two other bamboos. The physical and mechanical properties however have not fulfilled JIS A 5908 2003 yet. Differences in BP characteristics were caused by the chemical contents of bamboo, especially lignin that is different from species to species.